Global Marketing Strategy in Digital Era: Analysis The Use of Digital Marketing - Fitria Rahmadhani; Zidan Maulana; Muhammad Raviandra Antares; Mohamad Zein Saleh (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This article discusses global marketing strategies in the digital age, with a focus on the application of digital marketing. In the introduction, the phenomenon of digital marketing is explained as an important tool in reaching a vast global market. While many companies have successfully used digital marketing, others have failed due to a lack of understanding and proper strategy. Examples of publicly listed companies that have successfully implemented digital marketing will be outlined to provide a real-life illustration of this success. The importance of discussing digital marketing lies in its significant impact on the way companies interact with consumers around the world. The conclusion emphasizes that an in-depth understanding of digital marketing is key to success in global marketing, especially in facing challenges and taking advantage of opportunities.